Carcinoma in situ of the cervix and pregnancy - Seihet, Samoel (2015)
We have studied the histological structure of the cervix of 200 pregnant women with multiple biopsies taken during labor or immediately after him; then, in order to ascertain whether the histological changes found after señalaremos- which were permanent or only temporary and dependent on pregnancy, new biopsies 50 women, six and twelve weeks postpartum were taken, they are included in this group all wherein in the first biopsy showed these changes. In ten women (5%) histological alterations indistinguishable from carcinoma in situ was found; even in four of these cases they showed images suggestive of infiltration of the corium. In 18 women (9%) was found. nuclear atypia, which came to constitute some real monstrous cells. In 20 (10%) could be observed in cell disorder stratification and nuclear hyperchromatism. In 29 women (14.5%) increase in the number and size of nuclei in both the endo and ectocervix in was observed. In biopsies control post partum period was not possible to find the persistence of alterations described here; for this reason we conclude that these changes are not really carcinomas but transient changes caused by biological changes of pregnancy. The age of the pregnant woman, her condition primiparous or multiparous, and finally the number of previous births did not influence the development of the changes we have outlined. Finally hypertrophy was observed in the squamous epithelium of the ectocervix in 61 cases (30.5%), squamous metaplasia in the endocervix in 43 cases (21.5%), basal layer hyperplasia in 86 cases (43.0%), decirduales stromal changes in 21 cases (10.5%), and congestion and edema in 120 cases (60.0%). In most cases, these lesions have disappeared or dimmed in Control biopsies post partum; in these biopsies could observe however persistent chronic inflammatory changes, ie, cervicitis. The problem of diagnosis and treatment of carcinoma in situ of the cervix during pregnancy is discussed, and concluded that a diagnosis of intra-epithelial carcinoma of the cervix in a pregnant woman made is doubtful. In these circumstances you should expect to end the pregnancy to confirm through new biopsies and only then treat the patient.